2018
DOI: 10.21608/jpp.2018.36639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Yellow Maize Hybrids for Grain and Forage Yields Productivity

Abstract: The importance of cereal grains to nutrition of millions of people around the world is widely recognized. After wheat and rice, maize is the most important cereal grain in the world, providing nutrients for humans and animals. Maize silage is an important supplementary feed. The important characteristics of maize silage include high yield and high metabolically energy, but low protein content. Thus, two field experiments were carried out at the Experimental Farm of Gemmeiza Station, FCRI, ARC, Egypt, during su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…This is to be expected since such genotype recorded the highest values of stem and total dry weight/ plant as recorded in Table 3. These results were coincided by those obtained by Ali (2016), Balbaa & Awad (2018), Darwich (2018) and Mostafa (2018) who reported that yellow maize genotype namely S.C 168 was superior to other tested genotypes in grain yield/ fed.…”
Section: Yields/ Fed and Translocation Indicessupporting
confidence: 88%
See 1 more Smart Citation
“…This is to be expected since such genotype recorded the highest values of stem and total dry weight/ plant as recorded in Table 3. These results were coincided by those obtained by Ali (2016), Balbaa & Awad (2018), Darwich (2018) and Mostafa (2018) who reported that yellow maize genotype namely S.C 168 was superior to other tested genotypes in grain yield/ fed.…”
Section: Yields/ Fed and Translocation Indicessupporting
confidence: 88%
“…The differences among the tested maize genotypes in the growth characters may be attributed to the differences in their genetical makeup. In this connection, Darwich (2018) The interaction between the irrigation intervals and the tested maize genotypes was significant for leaf area/ plant in the first season and leaves dry weight/ plant in the second season. The differences among the tested genotypes for such traits were more pronounced when the plants were irrigated every days (normal irrigation) than they were irrigated every 17 and 22 days (moderate and severe stress drought), respectively.…”
Section: Growth Charactersmentioning
confidence: 78%